IMF-Supported Programs in Capital Account Crises : Design and Experience - Bulir, Ales (Occasional Papers; Occasional Paper ;, 2002)
This paper reviews the design of and experience with IMF-supported programs formulated in response to capital account crises in the 1990s, focusing on the experiences of eight countries: Turkey (1994), Mexico (1995), Argentina (1995), Thailand (1997), Indonesia (1997), Korea (1997), the Philippines (1997), and Brazil (1998). The capital account crises in emerging markets confronted both the affected countries and the IMF with a new set of challenges. The central feature of all these crises was the rapid reversal of capital inflows, bringing about a large and abrupt current account adjustment with pervasive macroeconomic consequences. The crises were characterized by an over-adjustment of external current accounts in relation to what was needed for any reasonable means of sustainability. This over-adjustment was associated with severe macroeconomic disruptions. Beyond the importance of crisis prevention, the experience of these countries suggests a number of lessons for program design in the context of high capital mobility-such as the appropriate roles for monetary, fiscal, and structural policies.